A comparative study of electrocoagulation and electro-Fenton for food industry wastewater treatment: Multiple response optimization and cost analysis. Issue 17 (22nd November 2018) - Varank, Gamze; Yazici Guvenc, Senem; Demir, Ahmet
ABSTRACT: In this study, response surface methodology was applied for food wastewater by electrocoagulation (EC) and electro-Fenton (EF) processes. The optimum conditions for the chemical oxygen demand (COD) removal were found to be 21.36 min, pH 10 and 86 mA/cm 2 in EC, whereas 27.11 min, pH 2.38, 86 mA/cm 2 and H2 O2 /COD:2 in EF process. COD removal efficiencies were determined to be 29.4% for EC and 59.1% for EF processes and higher than 99% total suspended solids removal efficiencies were achieved. It can be concluded that high COD removal was obtained (4998 mg/L COD removal by EC and 10, 047 mg/L COD removal by EF).